A Comparative Study on Residential Satisfaction in Relation to Spatial Characteristics of the Residential-Commercial Area in Urban Seoul Focused on the Analysis of Seorae Village of Banpo 4-dong and the Garosu-gil area of Sinsa-dong. Issue 2 (1st May 2017) - Kim, Ho-Jeong; Yang, Mi-Ran
Abstract : This study compares residential satisfaction in terms of local urban spatial characteristics between Seorae Village of Banpo 4-dong, and the Garosu-gil area of Sinsa-dong, both of which display distinct local identities and instances of mixed use. The results can be summarized as follows: First, residential satisfaction was higher in Seorae Village, Banpo 4-dong, than in the Garosu-gil area, Sinsa-dong, across all statistically significant criteria which were related to urban space characteristics such as the effective utilization of shared external space through block-unit development, independent territoriality of commercial and residential areas, qualitative completeness of green and street spaces. Second, the most influential factors affecting residential satisfaction were amenity, neighborhood, and safety in descending order, with amenity and safety showing a high degree of correlation. The amenity factor was significantly affected by the quality of transition areas situated between individual housing and urban space, and the neighborhood factor was closely related to community awareness. Third, while the commercialization of residential areas was largely regarded in a positive light, satisfaction regarding the street space in residential and commercial areas showed low correlation to overall residential satisfaction. Securing parking space and green space, and resolving the noise issue were identified as areas in need of improvement associated with the commercialization of residential areas, and they were major causes for residents in Sinsa-dong near the Garosu-gil area to relocate.